Identification of five Eimeria species in broiler farms in southern Thailand using SYBR Green-based real-time polymerase chain reaction - Baramee Chanchayanon; Somsak Pakpinyo; Kriengwich Limpavithayakul; Promwit Promvijit; Auntika Sriprad; Arithat Limsatanun (Frontiers in Animal Science)
IntroductionChicken coccidiosis is a globally significant poultry disease caused by Eimeria species, which are highly pathogenic protozoa that impair growth performance and contribute to high morbidity and mortality in the poultry industry. To identify specific Eimeria species, molecular techniques have been developed in several countries as alternatives to conventional diagnostic approaches, which are labor-intensive, time-consuming, and have low accuracy in detecting mixed infections.MethodsThis study aimed to develop a SYBR Green-based real-time polymerase chain reaction assay for the identification of Eimeria species in Thailand, using DNA from five reference species (E. acervulina, E. brunetti, E. maxima, E. necatrix, and E. tenella) and 25 field samples from broiler farms in southern Thailand.ResultsThe assay demonstrated high sensitivity, specificity, and reproducibility. Species-specific melting temperature profiles allowed reliable differentiation of Eimeria DNA from primer-dimers and potential contaminants. Field testing revealed a high prevalence of mixed infections, with E. tenella, E. acervulina, and E. maxima being the most common, whereas E. brunetti and E. necatrix were not detected.DiscussionCompared with conventional gross examination, the SYBR Green-based real-time polymerase chain reaction assay proved to be a more accurate and efficient tool for diagnosing coccidiosis in commercial broiler farms, particularly in detecting subclinical and mixed-species infections.